Contributing Factors to the Improvement of International Students' Health Literacy in China: A Self-Determination Theory Perspective - Zheng, Fuli; Hu, Pingying; Lian, Zhudan; Wang, Yuan-Liang; Wu, Siying; Li, Huangyuan (Frontiers in Public Health, 2020)
Background: It is generally accepted that learning engagement is predictive of better learning outcomes. Yet there might be some underlying motives for students to engage in or disengage from learning. Aims: Grounded in self-determination theory, this study aimed to examine whether satisfaction of international students’ innate needs for autonomy, competence and relatedness correlated positively with their engagement in learning and improvement of health literacy in China. Sample: Forty-three international undergraduates from a medical university in China participated in the study. Methods: Both qualitative and quantitative methods were used to deal with data collected from surveys on health literacy, perceived need satisfaction and the need satisfaction intervention, and from observation log recording dynamic changes in the students’ performance while implementing a need-satisfying scheme in Hygiene education. In addition, final examination scores of with/without-intervention parts were compared to unveil the effect of the intervention. Results: Perceived autonomy support motivated the participants to engage actively in learning; close relation to peers and teachers encouraged them to take on challenges; satisfying their need for competence enabled them to have better performance and academic achievements and to as well as an improvement on health literacy. Conclusions: The present study suggested that fulfillment of the students’ basic needs contributes to their engagement in learning and improvement of health literacy.